(untitled) (Modern education and development, 2025)
In recent years, Islamic finance has emerged as a significant alternative to conventional financial systems, driven by its ethical principles and risk-sharing mechanisms. Rooted in Shariah law, Islamic finance prohibits interest-based transactions (riba), speculative activities (gharar), and investments in harmful industries, making it an attractive option for both Muslim and non-Muslim investors seeking ethical financial solutions. With assets exceeding a huge amont globally, Islamic finance is no longer confined to predominantly Muslim nations but has gained traction in global financial hubs such as London, Hong Kong, and New York. This article explores the rise of Islamic finance, its fundamental principles, key financial instruments, and the challenges and opportunities shaping its future in an increasingly digital and interconnected world.